Treatment outcome of tuberculosis patients treated under DOTS in Calicut - Mohandas, Bindu; Pawar, Anant T.; John, Annie; Kumar, Durgesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Tuberculosis remains a worldwide public health problem despite the fact that highly effective drugs are available making TB a curable disease. DOTS chemotherapy remains central to the public health approach to tuberculosis control under RNTCP. The present study is conducted to know the clinical profile and treatment outcome of TB patients registered under RNTCP in Mukkam CHC, Calicut. The study was conducted with the following objectives: 1) to study the treatment outcome of TB patients receiving DOTS, 2) to find the occurrence of pulmonary, extra-pulmonary and MDR TB and 3) to find out factors responsible for poor treatment outcome. Methods: This record based study was conducted in Mukkam CHC. Details of patients who were enrolled under RNTCP in the year 2013 were collected from RNTCP records. Data was analyzed using SPSS version 16. Results are expressed in percentage. Statistical analysis used was Chi square test. Results: Out of 289 patients studied, 66.78% were males and 33.22% were females. 69.5% of the patients were having pulmonary TB and 30.5% extrapulmonary TB. There were two cases of MDR TB. 58% of the patients with pulmonary TB were sputum positive and 42% were sputum negative. 87.8% were given Cat I treatment and 11.7% were given Cat II treatment. Only one patient was on Non DOTS regimen. 96.6% of the patients had completed DOTS. When treatment outcome was analyzed, the patients with treatment completed was 54%, cured 35%, defaults 4%, treatment failure 2% and transfer out 2% and 3% of patients died during the course of the treatment. 7.61% of patients had diabetes mellitus and only one case was reported HIV positive. Treatment outcome was significantly associated with type of patient and pulmonary TB sputum positivity. Conclusions:The treatment success rate was 100% in 0-5 years and least in > 65years of age group. Further studies are required to find out the reasons for comparatively high proportion of sputum smear negative cases.